Risk Factors and Clinico-laboratory Characteristics of Scrub Typhus in Children Admitted to a Tertiary Pediatric Hospital of Nepal - Chapagain, Ram Hari; Adhikari, Santosh; Bista, Bihungum; Bhattarai, Tribhuwan; Thapa, Prabhat (Journal of Nepal Health Research Council, 2024)
Backgrounds: Scrub Typhus is a re-emerging illness with considerable morbidity and mortality and affected children have nonspecific sign symptoms. This study was conducted to find out the risk factors, clinical characteristics and laboratory profile and treatment outcome of scrub typhus among the children admitted in tertiary level pediatric hospital for febrile illness. Methods: A case control study was conducted among hospitalized children with acute febrile illness in a government pediatric referral hospital of central Nepal for two years (2021 to Sept 2023), who were tested using Scrub Typhus Antibody Rapid Test Kit. Results: We recruited 137 participants, comprising 68 cases of scrub typhus and 69 controls who had fever as a presenting complain, tested negative for scrub typhus and are matched with case in terms of age, gender, place of residence, and most importantly devoid of chronic health issues like leukemia, solid tumor, tuberculosis or kala-azar. Almost all cases i.e. 98.5% (n=67) had fever which is followed by abdominal pain 19.1% (n=13), headache 11.8%(n=8), vomiting 10.3%(n=7) and abdominal distension 8.8%(n=6). Hepatomegaly was commonest finding among scrub typhus positive cases comprising 50% (n=34) followed by lymphadenopathy 29.4% (n=20), splenomegaly 27.9% (n=19), eschar 17.6% (n=12) and rashes 10.3% (n=7). Cases having thrombocytopenia and leukocytosis were 51.5% (n=35) and 32.3% (n=22) respectively. Among scrub typhus cases, 17.6% (n=12) needed pediatric intensive care, 20.6% (n=14) had some sort of complications (i.e., meningitis, acute kidney injury, septic shock, acute respiratory distress syndrome), 46.3% (n=31) became afebrile within 24 hours of therapy, 29.8% (n=20) needed 48 hours to become afebrile. There were about 80% cases with the habit of taking naps on the ground. Those who reside other than cemented houses were with an increased risk factor of about 72%. Those who were not having good beds were at an increased risk factor of almost 100%. There were 62% of cases with bushes near their home and about 100% cases where they store animal fodder in their home. There were 63% who have any sort of animal in their bedroom. Conclusions: Engaging in agricultural work like working on fields, planting and livestock, working with bare hands/ feet, and having naps on the ground and living in houses made of mud dung and wood are the risk factors for the scrub factor. Fever, lymphadenopathy, hepatomegaly, splenomegaly are the common signs and symptoms and thrombocytopenia and increased levels of creatinine are the significant laboratory finding of scrub typhus in children. Keywords: Children; clinico-laboratory; Nepal; risk factor; scrub typhus.